Spatio-temporal relationship between carbon emission and ecosystem service value under land use change: a case study of the Guanzhong Plain Urban Agglomeration, China - Yang, Shuo; Zheng, Xiaozheng (Frontiers in Environmental Science, 2023)
Changes in land use restructuring significantly impact carbon emissions and the provision of ecosystem service value (ESV). This study focuses on the Guanzhong Plain Urban Agglomeration, and accounts for carbon emissions and ecosystem service values caused by land use in the years 2000, 2005, 2010, 2015, and 2020. Carbon sources, carbon sinks, net carbon emission intensity, and ESV intensity were introduced as research variables and the spatial and temporal divergence and correlation patterns between them were examined. The results show that: 1) The carbon emission intensity of land use in the Guanzhong Plain Urban Agglomeration has increased significantly over the study period, showing a distribution pattern of high intensity in the centra regions and low intensity in the surrounding regions. Construction land was identified as the largest carbon source. 2) The overall ESV follows an increasing trend, with the total value increasing from 215,263.7 million to 216,776.2 million. The distribution of ESV intensity is low in the central regions and high in the surrounding regions, and significant changes were observed in the ESV loss and gain intensity of farmland and water body. 3) Carbon emissions and ESV show a significant negative spatial correlation, and both are dominated by low-high and high-low aggregation patterns. A spatial spillover effect of carbon emissions on ESV was observed. Through the correlation analysis of carbon emissions and ESV, theoretical support is provided for promoting regional low-carbon green development and eco-economic synergistic development.